Performativities of Blackness: in search of a concept of Performative Black Theater (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
What is black performativity? What do black diasporic cosmoperceptions offer, beyond a mosaic of themes, for thinking about black performative theater in contemporary times? Seeking to think about black theaters beyond the trail left by dramaturgical anthologies published in recent decades, or by studies of black performance, this article, resulting from the work of the Black and Peripheral Performativity Research Group, sought to articulate, in a theoretical review and in dialogue with authors in the field, a concept of performative theater that reveals the vital force of the ways of doing, expressing, relating to, and feeling the world of black diasporic populations in Brazil.
Keywords: black performativities; blackness; black theaters